Can’t you find me? Female sexual response in an Argentinean tarantula (Araneae, Theraphosidae) - Copperi, Maria Sofia (2012)
We described and analyzed the female sexual response in the tarantula Grammostola vachoni Schiapelli and Gerschman 1961 under three series of 10 experiments each with different situations for the male-female encounters: male free in terrarium but with no access to female; male confined into a glass cup at 30 cm of female burrow and; male confined into a glass cup over a heavy stone closing the female burrow. We observed leg palpal tapping and body movements of female in response to male courtship. Leg and palpal tapping could indicate a female receptive condition and her attractiveness. Also, this behavior may serve to orient male towards her location. These females responded with leg and palpal tapping only to males which present long courtships together with active searching (walking) for female location. The female body movements, originated by legs III, are interpreted here as a rejection considering that male stopped courting and tried to escape.